Soil processes in sandy podzols under conditions of variations in climatic parameters of the forest steppe of the Central Russian province - N. P. Nevedrov; E. P. Protsenko; I. P. Balabina; M. Yu. Fomina; G. I. Popova (Юг России: экология, развитие)
Aim. The aim of the research was to identify the influence of the climate factor on the soil processes in sandy podzols in the forest‐steppe of the Central Russian province.Material and Methods. Traditional methods (soil survey method, profile method, microbiological methods, etc.) and the latest methods (direct measurements [in situ] of soil CO2 emission) of investigation were used.Results. It has been established that soil formation processes in azonal Al‐Fe‐humus sandy soils are reflexive to variations in climatic parameters of the forest‐steppe zone. In warmer and arid conditions of the forest‐steppe (southern part), sandy sod‐podzols are formed, in colder and humid conditions of the forest‐steppe (northern part) – sandy podzols. The soddy‐podzols of the southern part of the forest‐steppe can be characterized by a more humous soil profile, the content of which is 19.2% higher than in the sandy podzols. More over sod‐podzols have greater availability of mineral nutrition elements for plants and a higher microbiological activity (the number of bacteria is 12.7 times higher, micromycetes – 10.5 times, actinomycetes – 4.5 times) than sandy podzols. In summer, the rate of CO2 emission in Al‐Fe‐humus sandy soils in the northern part of the forest‐steppe zone reached 9.1 g CO2 m2/day, in the southern part – 12.5 g CO2 m2/day.Conclusion. Further climate changes, which have an arid trend in the forest‐steppe zone, can possibly lead to transformation of sandy podzols into sandy sod‐podzols.